(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
TABLE OF CONTENTS: 1. Premise - 2. Italy: the relevance of the possibility of satisfying religious feeling through the alternatives offered by computer tools - 3. Germany: the non-belonging of the public exercise of worship to the Wesensgehalt of the right to religious freedom - 4. France: the suspension of religious ceremonies as a “serious and manifestly unlawful interference” with religious freedom - 5. United States of America: the participation in religious services as the “heart of the First Amendment’s guarantee of religious liberty” - 6. Concluding remarks. ABSTRACT: The purpose of this paper is to examine the position and the scope of the right to religious freedom in the case law of the national courts of some European and non-European countries, which are called upon to establish the legitimacy or otherwise of the balancing realized by the emergency regulation against Covid-19 between this interest and the equally important one of health. Such evaluations, essentially conducted by the judges using the principle of proportionality (as well as that of reasonableness), betray, in fact, in the phase of verification of the adequacy of the measure (so-called Verhälntismäßigkeit im engeren Sinne) the identification of the sphere of intangibility within the right, removed from further balancing. The systems taken into consideration for this purpose are the Italian, German, French and American ones, identified as significant expressions of different regimes of relations between the State and religious denominations, and, therefore, tending to a different overall attitude of the State towards religious experience.